KOMPARASI EFEKTIFITAS STRATEGI PEMASARAN DESA WISATA KAMPUNG TERIH BATAM DAN DESA WISATA EKANG ANCULAI BINTAN - Asman Abnur; Armen Mustika; Eva Amalia (JURNAL MEKAR, 2023)
This study aims to compare the   marketing  strategy managed by   two similar tourist destinations in Batam  which is KampungTerih and the other one which in Bintan namely  Ekang Tourism Village  .  Kampung Terih and Ekang Tourism Village are tourist destinations that have the concept of a tourism village with beautiful nature and  various facilities as well tourist attraction. Both having positive arrival of visits which resulted from the marketing effort to attract visit intetntion. Using qualitative descriptive approach focusing on the marketing  development strategies to increase visitor levels are creating new innovations with the products offered so that tourists are more interested and curious and want to visit can go through  marketing platform to promoted the attractive tourism packages in describing  Kampung Terih and Desa Ekang Anculai  but does not eliminate the uniqueness and exclusivity of the village. Following strategis namely product introduction , promotion and repositioning and giving utmost service to visitor or tourist  effectively amongst of the best strategies to implement